Relationship of immunologic response to antiretroviral therapy with non-AIDS-defining cancer incidence - Yanik, Elizabeth L. (2014)
OBJECTIVE: To estimate the association between immunologic response to antiretroviral therapy (ART) and non-AIDS-defining cancer (NADC) incidence in HIV-infected patients. DESIGN: Prospective cohort including patients with ≥1 CD4 count and HIV-1 RNA measure after ART initiation between 1996 and 2011 in the Centers for AIDS Research Network of Integrated Clinical Systems, a collaboration of 8 HIV clinics at major academic medical centers in the United States. METHODS: Measures of immunologic response were six-month CD4 post-ART, latest CD4, and CD4 count-years, a cumulative measure of CD4 lymphopenia. Cox regression with inverse probability-of-exposure weights was used to calculate adjusted hazard ratios (HR) of virus-related and virus-unrelated NADC incidence. RESULTS: Among 9389 patients at ART initiation, median CD4 count was 200 cells/mm(3) (IQR=60–332), and median HIV-1 RNA was 4.8 log(10)copies/ml (IQR=4.3–5.4). Median follow-up was 3.3 years (IQR=1.5–6.5). After six months of ART, median CD4 count was 304 cells/mm(3) (IQR=163–469). 164 NADCs were diagnosed during study follow-up; 65 (40%) considered virus-related. Virus-related NADCs were inversely associated with six-month CD4 (HR per 100 cells/mm(3) increase=0.71), latest CD4 (HR per 100 cells/mm(3) increase=0.70), and CD4 count-years (HR per 200 cell-years/mm(3) increase=0.91) independent of CD4 at ART initiation, age, and HIV-1 RNA response. No associations were found with virus-unrelated NADCs. CONCLUSIONS: Poor CD4 response was strongly associated with virus-related NADC incidence, suggesting an important role for T-cell-mediated immunity in pathogenesis. Lower CD4 proximal to cancer diagnosis may be a result of subclinical cancer. Intensified cancer screening should be considered for patients on ART with low CD4 counts.